Optimization of clove flower oil extraction (Syzgium aromaticum L.) With Factorial Design Method - Muwaffaq, Muhammad Asror; Supriyo, Edy (Journal of Vocational Studies on Applied Research, 2021)
Solid-liquid extraction or commonly called leaching is the removal of the solute fraction (solute) from a solid to a liquid solvent. This extraction has become a widespread oil extraction process due to the high percentage of oil produced. Soxhletation method is an extraction method that contacts a solid and a liquid by dissolving it in the liquid phase at reflux. Clove oil is an essential oil that can be produced from distillation method on parts of the clove plant, especially the leaves and flowers of cloves. All parts of the clove plant contain oil, but the flowers contain the most oil. Because the leaves and twigs of cloves also produce oil, they also become a side income for clove farmers who harvest clove flowers for cigarettes. One of the most important ingredients in clove oil is eugenol, eugenol has many benefits from antiseptic to stimulant. Isopropyl alcohol is a unwell-known solvent specially to essential oil solvent, isopropyl alcohol is a solvent that can be recovered back into a solvent form usually using distillation method. The selection of isopropyl alcohol as a solvent is based on its high boiling point compared to other solvents and has elements of carbon, hydrogen, and oxygen that can dissolve polar molecules and their alkyl groups.